2016
DOI: 10.1016/j.jclepro.2016.02.142
|View full text |Cite
|
Sign up to set email alerts
|

Carbon emissions in a dual channel closed loop supply chain: the impact of consumer free riding behavior

Abstract: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
86
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(87 citation statements)
references
References 56 publications
1
86
0
Order By: Relevance
“…Bi et al (2016) considered green consumers in the supply chain and investigated the effects of subsidy policy of the government on firm decisions in two different situations [21]. investigated the carbon emissions in a dual channel closed loop supply chain, their research suggested that a government may have to subsidize the e-tailer to maximize the social welfare [22].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Bi et al (2016) considered green consumers in the supply chain and investigated the effects of subsidy policy of the government on firm decisions in two different situations [21]. investigated the carbon emissions in a dual channel closed loop supply chain, their research suggested that a government may have to subsidize the e-tailer to maximize the social welfare [22].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Previous studies addressed the effects of subsidy policies of the government using game theory [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. Despite the availability of these studies, only a few published articles explored the efficienci-es of subsidy policies of the government using game theory.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies investigated the issue by utilizing a case study or survey research [21]. Several studies investigated the issue by utilizing an analytical model in recent years [22][23][24][25][26][27][28][29][30]. Ghosh and Shah [22] developed an analytical model and studied the effect of channel structures on greening efforts and prices.…”
Section: Introductionmentioning
confidence: 99%
“…The findings can help policymakers predict the impact of normative policies on total carbon emissions in the supply chain operations. He et al [12] discussed the impact of free riding behavior of consumers and government taxes on carbon emissions in CLSC is analyzed. The results show that manufacturer can derive economic benefits from consumer free riding behavior, but the total carbon emissions in the whole supply chain are also increasing.…”
Section: Introductionmentioning
confidence: 99%